Currency Crisis - Islam, Faridul (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Financial crises are nothing new in the annals of history of the capitalistic path of economic development; indeed, they are part of business cycle. The theoretical basis for this is well entrenched in the concept of 'Keynesian Cross'. Tales of crises date back centuries, but have taken a new turn as the race for more globalization goes on, which involves liberalizing trade and opening up the financial sector. This has made many nations vulnerable to crises that are likely to be repeated, perhaps frequently. Based on recent experience, warning signs can be seen in the dollar-centric exchange rate, which is the mainstay for the stability of the current global financial system. To a careful observer, there is clearly fatigue in the system.